Analiza beril za 5. razred osnovne šole - Lah, Klemen (Slavistična revija, 2003)
The analysis of fifth-grade readers (Slovensko berilo I, Peta čitanka, Peto berilo Srečno, domovina, Pozdravlejeno, zeleno drevo, Kdo se skriva v ogledalu) focuses on revealing the covert content, i.e., the so-called hidden curriculum, within the period 1950-2000. The following categories were analyzed: texts, authors, literary characters, and other categories (differentcharacters, first-person narrator, warriors, mother and father).
Keywords: 1950/2000; berila; didactic method; didaktika; književnost; literature; osnovne šole